Pemberdayaan Pedagang Kecil Untuk Dapat Bertahan Pasca Pandemi Di Kelurahan Cibereum Kecamatan Cisarua Jawa Barat - Winaya Purwanti; Achmad Jaelani; Hastuti Indra Sari; Bambang Santosa; Rachmad Risqy Kurniawan; Asep Saefudin; Henny Risnawati (AMMA : Jurnal Pengabdian Masyarakat, 2023)
The COVID-19 pandemic has had a significant impact on the business sector, including small traders in the Cibereum District. Social restrictions, business closures, and shifts in consumer behavior have resulted in decreased income and economic difficulties for these small traders. The purpose of community service activities for small traders in the Cibereum District is to empower them to survive and recover after the pandemic. The outcomes of this community service include improving knowledge and skills. Collaboration between the government, community institutions, and small traders is a key factor in achieving effective empowerment. Utilizing digital technology and online platforms can help small traders overcome geographical limitations, enhance operational efficiency, and expand market reach.